Effect of Low-Fat Dairy Products Fortified with Encapsulated Vitamin D3 on Anxiety, Depression and Stress in People with Cardiovascular Risk Factors - Payam Sharifan; Hamideh Ghazizadeh; Susan Darroudi; Alireza Ghodsi; Sara Saffar Soflaei; Davoud Tanbacoochi; Mohammad Reza Fazl Mashhadi; Mohammad Amin Mohammadi; Ali Ebrahimi dabagh; Sara Moazedi; Maryam Mohammadi Bajgiran; Gordon Ferns; et al. (Journal of Nutrition and Food Security, 2024)
Vitamin D deficiency is a worldwide condition, which has been linked to a variety of health-related issues. Vitamin D can be beneficial to cardiovascular patients and those suffering from depression and anxiety, based on Survey of Ultraviolet Intake by Nutritional Approach (SUVINA study), ,showing the potential effects of vitamin D-fortified dairy products on anxiety, depression, and stress in subjects with cardiovascular disease (CVD) risk factors. Methods: It was a quadruple-blind randomized controlled trial. Individuals were randomly allocated to one of four groups: fortified low-fat milk (FM), non-fortified low-fat milk (NFM), fortified low-fat yogurt (FY), and non-fortified low-fat yogurt (NFY). FM and FY groups were fortified with 1500 IU nano-encapsulated vitamin D3. Anthropometric parameters as well as depression, anxiety, and stress scores were measured at baseline and after a ten-week trial in Mashhad, Iran. Results: Totally, 289 participants (143 men, 146 women) with a mean age of 41.86±7.81years were enrolled in the study. There was no statistical difference between the scores of depression, anxiety, and stress in participants with and without CVD risk factors (P>0.05).  No statistical difference was found in the subgroup analysis based on milk and yogurt consumption. Conclusions: Fortified low-fat milk containing 1,500 IU of vitamin D has no impact on improving depression, anxiety, and stress during ten weeks. However, further studies with higher vitamin D doses for a longer duration are recommended.